2022
DOI: 10.1159/000523689
|View full text |Cite
|
Sign up to set email alerts
|

Irisin Improves High-Fat Diet-Induced Sexual Dysfunction in Obese Male Rats

Abstract: Obesity is known to cause sexual dysfunction including erectile dysfunction and poor semen quality. Lifestyle modifications such as exercise have increasingly been more recognized to lower the likelihood of having sexual dysfunction or infertility in obese men. In this context, as an exercise-mimetic hormone, irisin have a potential to improve obesity-related reproductive dysfunctions. We aimed to elucidate possible effects of irisin on high-fat diet (HFD)-induced reproductive dysfunction in obese male rats. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 106 publications
0
6
0
Order By: Relevance
“…Testosterone replacement treatment in male functional hypogonadism, including patients with T2D, is associated with a significant increase in irisin concentration [ 241 ]. Conversely, peripheral but not intracerebral irisin administration improve testosterone levels and biologically related consequences such as sexual function and spermatogenesis [ 242 , 243 , 244 ].…”
Section: Future Directionsmentioning
confidence: 99%
“…Testosterone replacement treatment in male functional hypogonadism, including patients with T2D, is associated with a significant increase in irisin concentration [ 241 ]. Conversely, peripheral but not intracerebral irisin administration improve testosterone levels and biologically related consequences such as sexual function and spermatogenesis [ 242 , 243 , 244 ].…”
Section: Future Directionsmentioning
confidence: 99%
“…2 ). Considering previous studies illustrated that adipokines participated in the process of male infertility [ 32 , [53] , [54] , [55] , [56] ], we detected the adipokines level of DM mice after bezafibrate treatment and found that bezafibrate increased testicular adiponectin and irisin levels without affecting leptin and CTRP3 levels ( Fig. 1 G–J).…”
Section: Discussionmentioning
confidence: 94%
“…Evidence from animals to humans has reported that obesity plays a key role in male sexual dysfunction, including premature ejaculation and ED, although ED is mainly considered an age-related disease ( 21 , 22 ). It has been demonstrated not only that obesity is a strong and independent risk factor for ED but also that ED risk is positively correlated with the level of obesity ( 7 ).…”
Section: Discussionmentioning
confidence: 99%